Adsorption kinetics of a basic dye from aqueous solutions onto apricot stone activated carbon - Demirbas, E.; Kobya, M.; Sulak, M. T. (Elsevier Sci Ltd, 2008)
The preparation of activated carbon from apricot stone with H2SO4 activation and its ability to remove a basic dye, astrazon yellow 7GL, from aqueous solutions were reported in this study-The adsorbent was characterized by FTIR, BET and SEM, respectively. The effects of various experimental parameters, such as initial dye concentration, pH, adsorbent dosage and temperature were investigated in a batch-ad sorption technique. The optimum conditions for removal of the basic dye were found to be pH 10, 6 g/l of adsorbent dosage and equilibrium time of 35 min, respectively. A comparison of three kinetic models, the pseudo first-order, second-order and diffusion controlled kinetic models, on the basic dye-adsorbent system showed that the removal rate was heavily dependent on diffusion controlled kinetic models. The adsorption isotherm data were fitted well to Langmuir and Freundlich isotherms. The adsorption capacity was calculated as 221.23 mg/g at 50 degrees C. Thermodynamics parameters were also evaluated. The values of enthalpy and entropy were 49.87 kJ/mol and 31.93 J/mol K, respectively, indicating that this process was spontaneous and endothermic. The experimental studies were indicated that ASC had the potential to act as an alternative adsorbent to remove the basic dye from aqueous solutions. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: apricot stone carbon; low cost adsorbent; astrazon yellow; adsorption kinetics; adsorption equilibrium